MODEL PEMBELAJARAN PAI DALAM MENGEMBANGKAN SIKAP HUMANIS SISWA DI SMP NEGERI 2 REJANG LEBONG - Okni Aisa Mutiara Sendi; Dewi Purnama Sari; Jumira Warlizasusi; Asri Karolina; Sutarto Sutarto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
A humanistic state of mind can be created by guardians at domestic and instructors at school, one of which is through PAI learning. At SMP Negeri 2 Rejang Lebong understudies comprise of diverse ethnicities, societies and religions, these contrasts can trigger debate within the social life of understudies at school such as making companions with bunches, need of compassion to expect these issues, the PAI instructor at SMP N 2 Rejang Lebong creates a compassionate state of mind in PAI learning. The reason of this consider was to discover out the PAI learning demonstrate in creating the humanistic state of mind of understudies at SMP Negeri 2 Rejang Lebong. This consider employments a subjective strategy with a case ponder approach. The inquire about subjects were PAI instructors. This inquire about was conducted at SMP Negeri 2 Rejang Lebong in odd/even scholarly a long time. The information collection procedure utilized in this investigate is meet perception and documentation. The information investigation technique employments the hypothesis of Miles and Huberman and case ponder examination concurring to creswell. This concider concludes that the humanistic state of mind created in PAI learning at SMP Negeri 2 Rejang Lebong is isolated into five bunches, the primary is to regard the conclusion of others (shared regard, resilience, kindness), the moment is participation (taught), and the third is willing to give up. (duty), the fourth cares around the environment, the fifth makes a difference (mutual cooperation state of mind). PAi learning materials untilized in creating a humanist state of mind comprise of a few primary materials, to be specific the Qur’an and Hadith, moral theology, fiqh, ski. The learning demonstrate untilized by PAI instructors to create the humanistic demeanor of understudies at SMP Negeri 2 Rejang Lebong is the agreeable learning show, issue based learning, disclosure learning, relevant instructing and learning and drict instruction.